Implementation of the Lighting Test for the Homologation of Motorcycles and Tricycles According to the ISO 11460:2007 - Puente Moromenacho, Edwin Giovanny; Noroña Merchán, Marco Vinicio; Angulo Álvarez, Mishell Romina; Lincango Tite, Diego Luis (INGENIO, 2024)
The development of this essay addresses the issue of the application of the regulations international ISO 11460:2007 and its compliance for the evaluation of motorcycles and tricycles of the city of Quito, which is specifically related to the placement and lighting level of the lighting devices of these vehicles. For this reason, the main objective of the study is related to carrying out the test of illumination that is used for the homologation of motorcycles and tricycles according to the ISO 11460:2007 standard, for which five motorcycles taken from the market from the year 2019, assembled in the country and abroad, the same that will put in evidence the shortcomings and level of compliance observed in the motorcycles that make up the sample for the investigation, whose results will allow establishing the current reality of this problematic. An adequate procedure was carried out for the evaluation of motorcycles in the lighting test, as well as the approach, methods and instruments that allowed analyze and collect information according to the guidelines set forth. Subsequently, in the results obtained from the lighting test and the data from the ISO 11460:2007 standard, showing that the 5 evaluated motorcycles disobey said standard in some of their lighting fixtures.